Optimizing Digital Image Steganography to Enhance the Security of Secret Message Delivery - Eko Heri Susanto; Dimas Pramudya Pratama; Ricki Septian Nurpratama (International Journal of Engineering Continuity, 2024)
Image steganography is a technique used to hide secret messages in image media. In this research, 2 method improvements are proposed, namely (1) layered message security utilizing vigenere encryption with asymmetric keys, and (2) optimizing the hiding capacity (HC) of secret messages, utilizing the bit shift operation method. From the test results it can be proven that layered message security has been successfully implemented, and the capacity of secret messages can be increased. From the initial 4 bits per pixel it increased to 8 bits per pixel. However, the steganography image quality of the proposed method is not better than the PVDMF method.